PEMBAHARUAN HUKUM PIDANA TERHADAP PENYALAHGUNAAN KARTU KREDIT DI INDONESIA - Wiwik Sri Widiarty (to-ra, 2016)
Credit Card is tools in the form of plastic cards, is one of banking products that the user indicates that growth continues to increase, with the number of payments this intermediate level, where a credit card actually facilitate customer transactions by swiping when the bill arrived. The ease of shopping by using a credit card can increase sales turnover for the merchant itself. Likewise, the number of traders who are interested in serving transactions using credit cards tend to increase. For certain segments of society, credit cards have been a requirement by the day to make transactions because they do not need to carry cash (cash), but credit cards also pose its own risks for the cardholder, with the increase of credit card users, giving rise to the occurrence of abuse credit cards by parties who are not responsible. Misuse of credit cards including those that are difficult to overcome, since the law in Indonesia has been no specific regulations governing punitive sanctions against this crime. Lately increasingly widespread misuse of credit cards, including in Indonesia. In order to combat the use of credit cards, it must be possible reform of criminal law against the misuse of credit cards, with the reform of criminal law in accordance with the values and spirit of the Indonesian people at this time.Kata kunci: Pembaharuan Hukum Pidana dan Penyalahgunaan Kartu Kredit